Nostalgia and bonds: Exploring themes of friendship, family, and love in K-drama “Reply 1988” - Wajdi, Majid; Joaquin, Cleo Jude; Ayub, Sadia; Mustafa, Muhammad; Uzma, Sidratul Muntaha (Yayasan Mitra Persada Nusantara, 2025)
This study explores the core themes of friendship, family, and love in the South Korean television drama Reply 1988. As part of the acclaimed “Reply” series, Reply 1988 revisits the late 1980s in a Seoul neighbourhood, presenting deeply personal and social dynamics through the everyday lives of five families. The objective of this research is to analyse how the drama portrays emotional and cultural values, especially emphasizing the interplay between communal living, generational understanding, and interpersonal affection. Using a qualitative descriptive method, this study employs content analysis by observing narrative structures, character development, and key dialogues within the 20-episode series. Through close reading and thematic categorization, the study identifies motifs such as sacrifice, loyalty, unspoken affection, and the warmth of familial bonds. The analysis reveals that Reply 1988 effectively humanizes historical nostalgia, portraying the 1980s as a period of sincere social interaction and collective identity. The theme of friendship is illuminated through the enduring bond among the neighbourhood’s children, while family dynamics are shown through intergenerational respect and emotional dependence. Romantic love, subtle and often secondary, highlights the slow, realistic evolution of relationships. In conclusion, Reply 1988 transcends conventional melodrama by offering viewers a textured representation of Korean society through universal emotions. It serves not only as entertainment but also as cultural reflection, resonating with audiences globally through its sincere depiction of everyday life and timeless values.